In Vivo Cytochrome P450 3A Isoenzyme Activity and Pharmacokinetics of Imatinib in Relation to Therapeutic Outcome in Patients With Chronic Myeloid Leukemia. Issue 2 (April 2016) - Skoglund, Karin; Richter, Johan; Olsson-Strömberg, Ulla; Bergquist, Jonas; Aluthgedara, Warunika; Ubhayasekera, S. J. Kumari A.; Vikingsson, Svante; Svedberg, Anna; Söderlund, Stina; Sandstedt, Anna; Johnsson, Anders; Aagesen, Jesper; et al.
Abstract : Background: Cytochrome P450 3A (CYP3A) isoenzyme metabolic activity varies between individuals and is therefore a possible candidate of influence on the therapeutic outcome of the tyrosine kinase inhibitor imatinib in patients with chronic myeloid leukemia (CML). The aim of this study was to investigate the influence of CYP3A metabolic activity on the plasma concentration and outcome of imatinib in patients with CML. Methods: Forty-three patients with CML were phenotyped for CYP3A activity using quinine as a probe drug and evaluated for clinical response parameters. Plasma concentrations of imatinib and its main metabolite, CGP74588, were determined using liquid chromatography–mass spectrometry. Results: Patients with optimal response to imatinib after 12 months of therapy did not differ in CYP3A activity compared to nonoptimal responders (quinine metabolic ratio of 14.69 and 14.70, respectively; P = 0.966). Neither the imatinib plasma concentration nor the CGP74588/imatinib ratio was significantly associated with CYP3A activity. Conclusions: The CYP3A activity does not influence imatinib plasma concentrations or the therapeutic outcome. These results indicate that although imatinib is metabolized by CYP3A enzymes, this activity is not the rate-limiting step in imatinib metabolism and excretion. Future studies should focus on other pharmacokinetic processes so as to identify the major contributor to patient variability in imatinib plasma concentrations. Abstract : Supplemental Digital Content is Available in the Text.